A barium titanate-titanium dioxide composite scaffold based on light-cured 3D printing and a preparation method and application thereof

CN122940474APending Publication Date: 2026-10-20WUHAN UNIV OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202610892919.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-21
Publication Date
2026-10-20

AI Technical Summary

Benefits of technology

(1)本发明采用光固化3D打印制备三维周期多孔钛酸钡陶瓷支架,可实现支架外形、孔道结构及局部几何特征的较精确构建,所得支架孔道连续、结构规则且表面质量较好,有利于前驱体溶液充分浸润复杂三维表面及内孔壁,并为后续二氧化钛的异相成核和原位生长提供稳定载体;对于压电-光催化应用,该类连续多孔结构还有利于反应物传质、光进入孔道以及机械振动作用下应力在支架中的传递,从而为压电效应与光催化效应的协同发挥提供结构基础。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention relates to the fields of functional materials and photopolymer additive manufacturing technology, specifically to a barium titanate-titanium dioxide composite scaffold based on photopolymer 3D printing, its preparation method, and its application. The method includes: preparing a barium titanate photosensitive slurry, photopolymerizing and 3D printing it, and then debinding and sintering it to obtain a barium titanate scaffold; then, using ethylene glycol methyl ether, tetrabutyl titanate, and glycerol as precursors, solvothermal in-situ growth of titanium dioxide nanowires, followed by annealing to obtain the composite scaffold. This invention utilizes photopolymer 3D printing to obtain a three-dimensional porous barium titanate scaffold with a regular structure and continuous pores, providing a stable carrier for precursor wetting and surface growth; the ethylene glycol methyl ether system inhibits the excessively rapid homogeneous reaction of the titanium source, promotes controlled growth of titanium dioxide on the scaffold surface, and improves the uniformity of active component distribution and the quality of heterogeneous interface construction. The resulting composite scaffold is easy to separate and recover, structurally stable, and can degrade organic dyes through photopolymerization and mechanical vibration coupling.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the fields of functional materials and photopolymer additive manufacturing technology, specifically to a barium titanate-titanium dioxide composite scaffold based on photopolymer 3D printing, its preparation method, and its application. Background Technology

[0002] Nanocatalytic materials typically possess high catalytic activity due to their large specific surface area and abundant active sites. However, nanoparticles are prone to agglomeration in liquid systems and are difficult to separate and recover after the reaction, limiting their engineering applications. Constructing catalytically active components on the surface of recyclable three-dimensional porous ceramic scaffolds is an effective way to improve the recyclability and structural stability of catalysts. Additive manufacturing technology enables the transition of catalysts from powder form to customized three-dimensional complex porous structures, facilitating the customized design of catalytic scaffolds. Among various additive manufacturing technologies, photopolymerization 3D printing has attracted significant attention due to its high forming accuracy and good surface quality. This technology is particularly suitable for manufacturing ceramic devices with fine microscopic features and complex three-dimensional porous geometries, and is of great significance for constructing piezoelectric-photocatalytic scaffolds with large specific surface areas, continuous channels, and adjustable local stress distribution.

[0003] In the prior art, patent publication number CN114195511A, entitled "Preparation Method and Application of Barium Titanate Ceramic Scaffold with Surface Hydrothermal Growth of Titanium Dioxide Nanowire Array," utilizes direct ink writing 3D printing technology to prepare a woodpile structure barium titanate scaffold, and then grows titanium dioxide nanowires on the scaffold surface via a hydrothermal method for catalytic degradation of dyes. However, direct ink writing 3D printing technology itself has inherent limitations in terms of forming accuracy and surface quality. Furthermore, during the growth of titanium dioxide nanowires, the titanium source is prone to premature reaction in conventional alcohol systems, leading to particulate precipitation before or in the early stages of the reaction. This is detrimental to the formation of uniform one-dimensional nanowires in subsequent reactions, potentially forming aggregated particles or micron-sized flowers, thus affecting the stability and reproducibility of catalytic performance.

[0004] Therefore, it is necessary to provide a method for preparing complex three-dimensional porous barium titanate-titanium dioxide ceramic composite scaffolds to fully realize their potential in piezoelectric photocatalysis applications. Summary of the Invention

[0005] In view of this, the present invention provides a barium titanate-titanium dioxide composite scaffold based on photopolymerization 3D printing, its preparation method, and its application. The core lies in using high-precision photopolymerization technology to achieve the integrated forming of complex porous structures, and utilizing an ethylene glycol methyl ether solvent system to effectively suppress the hydrolysis of the titanium source, thereby reliably growing a one-dimensional titanium dioxide nanowire structure with a high specific surface area on the scaffold surface. This composite material successfully combines structural design, piezoelectric effect, and photocatalysis, providing a high-performance and easily recyclable solution for the efficient degradation of organic pollutants, overcoming the limitations of structural precision in existing three-dimensional barium titanate scaffolds used for catalytic degradation and the poor controllability of in-situ growth of titanium dioxide nanowires.

[0006] The technical solution of this invention is implemented as follows: In a first aspect, the present invention provides a method for preparing a barium titanate-titanium dioxide composite scaffold based on photopolymerization 3D printing, comprising the following steps: S1: Using photopolymerization 3D printing technology, a three-dimensional porous ceramic blank is prepared from a photosensitive slurry containing barium titanate powder; S2: Degreasing, carbon removal and sintering are performed on the three-dimensional porous ceramic green body to obtain a three-dimensional porous barium titanate ceramic scaffold. S3: Immerse the three-dimensional porous barium titanate ceramic scaffold in a precursor solution containing a titanium source, ethylene glycol methyl ether, and glycerol for a solvothermal reaction; S4: Annealing the scaffold after the solvothermal reaction yields a barium titanate-titanium dioxide composite scaffold with in-situ grown titanium dioxide nanowires on the surface.

[0007] Preferably, in step S1, the volume fraction of barium titanate powder in the photosensitive paste is 45-55 Vol%, and the average particle size of the barium titanate powder is 200-300 nm.

[0008] Preferably, the components of the photosensitive paste further include trimethylolpropane triacrylate (TMPTA), 1,6-hexanediol diacrylate (HDDA), polypropylene glycol (PPG), a photoinitiator, a dispersant, and a rheology modifier; the photoinitiator includes diphenyl (2,4,6-trimethylbenzoyl)phosphine oxide (TPO), the dispersant includes KMT-3331, and the rheology modifier includes BYK-405.

[0009] More preferably, the mass ratio of TMPTA:HDDA:PPG:TPO:KMT-3331:BYK-405 is approximately 4:4:3:0.3:1.5:0.6.

[0010] Preferably, in step S1, the exposure energy density of the photopolymerization 3D printing is 55~265 mJ / cm². 2The scanning interval is 0.02~0.03 mm, and the layer thickness is 30 μm; in step S2, the degreasing is carried out in an argon atmosphere, and the carbon removal and sintering are carried out in an air atmosphere.

[0011] More preferably, in step S2, the degreasing process is as follows: starting from room temperature (25 ℃), the temperature is increased at 0.5 ℃ / min to 150 ℃ and held for 2 h; then increased at 0.5 ℃ / min to 250 ℃ and held for 2 h; then increased at 0.5 ℃ / min to 350 ℃ and held for 2 h; then increased at 0.5 ℃ / min to 500 ℃ and held for 2 h; then increased at 0.5 ℃ / min to 600 ℃ and held for 2 h; and finally cooled naturally to room temperature. The carbon removal and sintering process is as follows: starting from room temperature, the temperature is increased at 1 ℃ / min to 450 ℃ and held for 2 h; then increased at 1 ℃ / min to 600 ℃ and held for 2 h; then increased at 3 ℃ / min to 1325 ℃ and held for 2 h; and finally cooled naturally to room temperature.

[0012] Specifically, by adjusting the heating rate and holding time during the degreasing and carbon removal sintering process, it can be ensured that the support structure is not damaged.

[0013] Preferably, in step S3, the titanium source includes tetrabutyl titanate, the concentration of tetrabutyl titanate in the precursor solution is 0.05~0.15 mol / L, and the volume ratio of ethylene glycol methyl ether to glycerol is 2~3:1, more preferably 2.3:1.

[0014] Specifically, when the volume ratio of ethylene glycol methyl ether to glycerol is too low, the ethylene glycol methyl ether content is insufficient, reducing the stability of the titanium precursor and making it prone to rapid homogeneous reactions, resulting in particulate precipitation or local agglomeration. Simultaneously, an excessively high glycerol ratio increases the system viscosity, hindering the precursor solution from fully wetting the pores and pore walls of the scaffold. When the volume ratio of ethylene glycol methyl ether to glycerol is too high, the structure-directing effect of glycerol is insufficient, weakening the one-dimensional growth of titanium dioxide and leading to sparse, short, discontinuous nanowires or insufficient active layer loading. Therefore, when the volume ratio of ethylene glycol methyl ether to glycerol is controlled at 2–3:1, especially approximately 2.3:1, a better balance can be struck between the stability of the titanium precursor, the wettability of the scaffold pores, and the structure-directing effect of glycerol, thereby obtaining a uniformly distributed, stably adhered titanium dioxide nanowire layer with an open network structure on the surface of a three-dimensional porous barium titanate scaffold.

[0015] More preferably, in step S3, tetrabutyl titanate is first added to the beaker, followed by ethylene glycol methyl ether as a coordination organic solvent. After stirring evenly, glycerol, a structure-directing agent, is added, and the mixture is stirred and sonicated to maintain a relatively stable dispersion of the titanium precursor before the reaction, which is beneficial for the subsequent controlled in-situ growth on the surface of the three-dimensional porous barium titanate scaffold and the pore wall surface.

[0016] Preferably, in step S3, the temperature of the solvothermal reaction is 160~200 °C, and the reaction time is 24 h.

[0017] Preferably, in step S4, the annealing temperature is 350~450 ℃ and the holding time is 1~2 h.

[0018] Preferably, after the solvothermal reaction in step S3 and before the annealing treatment in step S4, a stepwise drying step is also included: first, keeping the temperature at 60°C for 12~24 h, and then keeping the temperature at 80°C for 12~24 h.

[0019] In a second aspect, the present invention provides a barium titanate-titanium dioxide composite scaffold prepared by the preparation method described in the first aspect.

[0020] Thirdly, the present invention provides the application of the barium titanate-titanium dioxide composite scaffold as described in the second aspect in the degradation of organic pollutants, wherein the degradation is carried out under conditions of light and mechanical vibration, and the organic pollutants include Rhodamine B.

[0021] Compared with the prior art, the advantages of the present invention are as follows: (1) The present invention uses photopolymerization 3D printing to prepare three-dimensional periodic porous barium titanate ceramic scaffolds, which can achieve relatively accurate construction of scaffold shape, pore structure and local geometric features. The resulting scaffold has continuous pores, regular structure and good surface quality, which is conducive to the full wetting of complex three-dimensional surface and inner pore wall by precursor solution, and provides a stable carrier for subsequent heterogeneous nucleation and in-situ growth of titanium dioxide. For piezoelectric-photocatalytic applications, this type of continuous porous structure is also conducive to reactant mass transfer, light entering the pores and stress transmission in the scaffold under mechanical vibration, thus providing a structural basis for the synergistic effect of piezoelectric effect and photocatalytic effect.

[0022] (2) The present invention uses an ethylene glycol methyl ether-glycerol precursor system for nanowire growth. Ethylene glycol methyl ether helps to reduce the excessively rapid homogeneous reaction of tetrabutyl titanate before or in the early stage of the reaction, reduce the formation of particulate precipitates and agglomerates, and make the titanium precursor more conducive to controlled heterogeneous nucleation and one-dimensional growth on the surface of barium titanate scaffold and pore wall surface. Glycerol further plays a structural guiding and stabilizing role, which is conducive to the formation of a more uniformly distributed and more stably attached titanium dioxide nanowire layer, which more effectively increases the specific surface area and active sites of the scaffold, thereby improving the piezoelectric-photocatalytic performance of the scaffold. Attached Figure Description

[0023] Figure 1 This is a flowchart of the preparation steps of the method of the present invention; Figure 2These are comparative images of the surface morphology of samples prepared in Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3, and Comparative Example 4 of the present invention. Among them, (a), (b), and (c) are scanning electron microscope images of the surface of the sample prepared in Example 1; (d), (e), and (f) are scanning electron microscope images of the surface of the sample prepared in Comparative Example 1; and (g), (h), and (i) are scanning electron microscope images of the surface of the samples prepared in Comparative Example 2, Comparative Example 3, and Comparative Example 4. Figure 3 The images shown are scanning electron microscope (SEM) images of the samples prepared by varying the concentration of tetrabutyl titanate in Examples 4-7 of this invention. (a) and (b) are SEM images at a tetrabutyl titanate concentration of 0.05 mol / L; (c) and (d) are SEM images at a tetrabutyl titanate concentration of 0.08 mol / L; (e) and (f) are SEM images at a tetrabutyl titanate concentration of 0.12 mol / L; and (g) and (h) are SEM images at a tetrabutyl titanate concentration of 0.15 mol / L. Figure 4 The graph shows the degradation results of 100 mL of 10 mg / L Rhodamine B (RhB) solution by different samples under light and ultrasonic conditions. BT is the three-dimensional porous ceramic scaffold prepared in step (4) of Example 1, EG-BT is the composite scaffold prepared in Example 1, and ET-BT is the three-dimensional porous ceramic scaffold prepared in Comparative Example 1. (a) shows the self-degradation of RhB solution and the degradation rate of RhB solution by different samples; (b) shows the corresponding fitting apparent first-order kinetic constant comparison graph. Figure 5 The diagram shows the preliminary reaction process of titanium source precursor under different solvent systems, where (1) is the ethanol system; (2) and (3) are the ethylene glycol methyl ether system. Detailed Implementation

[0024] Embodiments of the present invention are described in detail below, examples of which are illustrated in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to explain the present invention, and should not be construed as limiting the present invention.

[0025] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of indicated technical features. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include one or more of that feature. Furthermore, in the description of this invention, unless otherwise stated, "a plurality of" means two or more.

[0026] In this document, the terms “containing,” “comprising,” or “including” are open-ended expressions, meaning they include the contents specified in this invention but do not exclude other aspects.

[0027] In this document, the terms “optional,” “optionally,” or “optional” generally refer to an event or condition that may, but may not, occur, and the description includes both cases in which the event or condition occurs and cases in which the event or condition does not occur.

[0028] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the protection scope of the present invention.

[0029] Unless otherwise specified, all raw materials used in this invention are purchased from the market, and all purchased chemicals are used directly without purification. Among them, tetrabutyl titanate, glycerol, ethylene glycol methyl ether, trimethylolpropane triacrylate (TMPTA), and diphenyl (2,4,6-trimethylbenzoyl)phosphine oxide (TPO) were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; 1,6-hexanediol diacrylate (HDDA) was purchased from Shanghai Yinchang New Materials Co., Ltd.; KMT-3331 was purchased from Foshan Kening New Materials Co., Ltd.; BYK-405 was purchased from BYK Chemical Co., Ltd.; and polypropylene glycol (PPG) and barium titanate (particle size 200~300 nm) were purchased from Shanghai Maclean Biochemical Technology Co., Ltd.

[0030] Example 1 This embodiment provides a barium titanate-titanium dioxide composite scaffold based on photopolymerization 3D printing and its preparation method. The overall process is as follows: Figure 1 As shown, it includes the following steps: Photopolymerization 3D printing of barium titanate three-dimensional porous ceramic scaffolds (BT) (1) Weigh 4.3 g KMT-3331, 1.7 g BYK-405, 11.15 g TMPTA, 8.36 g HDDA, 8.36 g PPG and 0.86 g TPO in sequence, then stir magnetically for 15 min to mix evenly, then add to 200 g barium titanate ceramic powder, and ball mill at 350 r / min for 8 h to obtain 50 Vol% barium titanate photosensitive paste; (2) The slurry obtained above was transferred to a photopolymerization 3D printer with a laser wavelength of 405 nm for printing to obtain a porous ceramic blank; the main printing process parameters included: scanning speed 3000 mm / s, scanning spacing 0.03 mm, layer thickness 30 μm, and exposure energy density 215 mJ / cm². 2 After printing, the residual slurry on the surface and in the pores of the blank is cleaned and dried at 60 ℃ for 6 h; (3) Place the obtained green blank in a tube furnace and degrease it under an inert atmosphere. The degreasing process requires slow heating. The specific steps are as follows: heat up to 150 ℃ from room temperature at 0.5 ℃ / min and hold for 2 h; heat up to 250 ℃ at 0.5 ℃ / min and hold for 2 h; heat up to 350 ℃ at 0.5 ℃ / min and hold for 2 h; heat up to 500 ℃ at 0.5 ℃ / min and hold for 2 h; heat up to 600 ℃ at 0.5 ℃ / min and hold for 2 h to complete the degreasing. Then cool it with the furnace. (4) The degreased sample was placed in a muffle furnace and decarbonized and sintered in an air atmosphere. The specific steps were as follows: the temperature was increased from room temperature to 450 ℃ at 1 ℃ / min and held for 2 h; the temperature was increased to 600 ℃ at 1 ℃ / min and held for 2 h to complete the decarbonization; the temperature was increased to 1325 ℃ at 3 ℃ / min and held for 2 h; and the sample was cooled with the furnace to complete the sintering and densification of the barium titanate porous ceramic and obtain the barium titanate three-dimensional porous ceramic scaffold (BT). In-situ growth of titanium dioxide nanowires on barium titanate ceramic surface (5) Add 0.005 mol tetrabutyl titanate and 35 ml ethylene glycol methyl ether to a beaker, stir the mixture for 5 min, then add 15 ml glycerol, continue stirring for 5 min, then sonicate for 5 min, and transfer the mixture to a high-pressure reactor, wherein the concentration of tetrabutyl titanate in the precursor solution is 0.1 mol / L; completely immerse the barium titanate three-dimensional porous ceramic scaffold from step (4) into the reactor solution; (6) Place the high-pressure reactor in a solvothermal environment at 180 °C for 24 h, and remove the support after natural cooling. Wash and dry the support with ethanol. The drying should be done at low temperature to avoid the nanowires from collapsing due to excessive evaporation of organic solvent. The specific steps are: dry at 60 °C for 24 h and dry at 80 °C for 24 h. (7) The dried support was placed in a muffle furnace and heated to 400 ℃ at 3 ℃ / min from room temperature. The temperature was held for 1 h and then cooled with the furnace to complete the annealing, thus obtaining a barium titanate three-dimensional porous ceramic support (EG-BT) with titanium dioxide nanowires grown on the surface.

[0031] like Figure 2As shown in (a), (b), and (c) in the figure, the titanium dioxide nanowires synthesized using the ethylene glycol methyl ether solvent system in Example 1 are uniformly distributed on the surface of the barium titanate porous ceramic scaffold, and the nanowires are clearly visible.

[0032] Example 2 This embodiment provides a barium titanate-titanium dioxide composite scaffold based on photopolymerization 3D printing and its preparation method, including the following steps: Photopolymerization 3D printing of barium titanate three-dimensional porous ceramic scaffolds (BT) (1) Weigh 4.3 g KMT-3331, 1.7 g BYK-405, 11.15 g TMPTA, 8.36 g HDDA, 8.36 g PPG and 0.86 g TPO in sequence, then stir magnetically for 15 min to mix evenly, then add to 163.6 g barium titanate ceramic powder, and ball mill at 350 r / min for 8 h to obtain 45 Vol% barium titanate photosensitive paste; (2) The slurry obtained above was transferred to a photopolymerization 3D printer with a laser wavelength of 405 nm for printing to obtain a porous ceramic blank; the main printing process parameters included: scanning speed 3000 mm / s, scanning spacing 0.03 mm, layer thickness 30 μm, and exposure energy density 265 mJ / cm². 2 After printing, the residual slurry on the surface and in the pores of the blank is cleaned and dried at 60 ℃ for 6 h; (3) The obtained green blank was placed in a tube furnace and degreased under an inert atmosphere. The degreasing process was the same as in Example 1. (4) The degreased sample was placed in a muffle furnace and carbonized and sintered in an air atmosphere. The specific steps were the same as in Example 1. In-situ growth of titanium dioxide nanowires on barium titanate ceramic surface (5) Add 0.005 mol tetrabutyl titanate and 33.3 ml ethylene glycol methyl ether to a beaker, stir the mixture for 5 min, then add 16.7 ml glycerol, continue stirring for 5 min, then sonicate for 5 min, and transfer the mixture to a high-pressure reactor, wherein the concentration of tetrabutyl titanate in the precursor solution is 0.1 mol / L; completely immerse the barium titanate three-dimensional porous ceramic scaffold from step (4) into the reactor solution; (6) Place the high-pressure reactor in a solvothermal environment at 160 °C for 24 h, and remove the support after natural cooling; wash and dry the support with ethanol. The drying should be done at low temperature to avoid the nanowires from collapsing due to excessive evaporation of organic solvent. The specific steps are: dry at 60 °C for 12 h and dry at 80 °C for 24 h. (7) Place the dried support in a muffle furnace, raise the temperature to 450 ℃ from room temperature at 3 ℃ / min, hold for 1 h, cool with the furnace to complete the annealing, and obtain a barium titanate three-dimensional porous ceramic support with titanium dioxide nanowires grown on the surface.

[0033] Example 3 This embodiment provides a barium titanate-titanium dioxide composite scaffold based on photopolymerization 3D printing and its preparation method, including the following steps: Photopolymerization 3D printing of barium titanate three-dimensional porous ceramic scaffolds (BT) (1) Weigh 4.3 g KMT-3331, 1.7 g BYK-405, 11.15 g TMPTA, 8.36 g HDDA, 8.36 g PPG and 0.86 g TPO in sequence, then stir magnetically for 15 min to mix evenly, then add to 244.4 g barium titanate ceramic powder, and ball mill at 350 r / min for 8 h to obtain 55 Vol% barium titanate photosensitive paste; (2) The slurry obtained above was transferred to a photopolymerization 3D printer with a laser wavelength of 405 nm for printing to obtain a porous ceramic blank; the main printing process parameters included: scanning speed 3000 mm / s, scanning spacing 0.02 mm, layer thickness 30 μm, and exposure energy density 55 mJ / cm². 2 After printing, the residual slurry on the surface and in the pores of the blank is cleaned and dried at 60 ℃ for 6 h; (3) The obtained green blank was placed in a tube furnace and degreased under an inert atmosphere. The degreasing process was the same as in Example 1. (4) The degreased sample was placed in a muffle furnace and carbonized and sintered in an air atmosphere. The specific steps were the same as in Example 1. In-situ growth of titanium dioxide nanowires on barium titanate ceramic surface (5) Add 0.005 mol tetrabutyl titanate and 37.5 ml ethylene glycol methyl ether to a beaker, stir the mixture for 5 min, then add 12.5 ml glycerol, continue stirring for 5 min, then sonicate for 5 min, and transfer the mixture to a high-pressure reactor, wherein the concentration of tetrabutyl titanate in the precursor solution is 0.1 mol / L; completely immerse the barium titanate three-dimensional porous ceramic scaffold from step (4) into the reactor solution; (6) Place the high-pressure reactor in a solvothermal environment at 200 °C for 24 h, and remove the support after natural cooling. Wash and dry the support with ethanol. The drying should be done at a low temperature to avoid the nanowires from collapsing due to excessive evaporation of organic solvents. The specific steps are: dry at 60 °C for 24 h and dry at 80 °C for 12 h. (7) Place the dried support in a muffle furnace, raise the temperature to 350 ℃ from room temperature at 3 ℃ / min, hold for 2 h, cool with the furnace to complete the annealing, and obtain a barium titanate three-dimensional porous ceramic support with titanium dioxide nanowires grown on the surface.

[0034] Example 4 The difference between this embodiment and Example 1 is that 0.0025 mol of tetrabutyl titanate is added in step (5); the rest remains the same, that is, the concentration of tetrabutyl titanate in the precursor solution is 0.05 mol / L.

[0035] Example 5 The difference between this embodiment and Example 1 is that 0.004 mol of tetrabutyl titanate is added in step (5); the rest remains the same, that is, the concentration of tetrabutyl titanate in the precursor solution is 0.08 mol / L.

[0036] Example 6 The difference between this embodiment and Example 1 is that 0.006 mol of tetrabutyl titanate is added in step (5); the rest remains the same, that is, the concentration of tetrabutyl titanate in the precursor solution is 0.12 mol / L.

[0037] Example 7 The difference between this embodiment and Example 1 is that 0.0075 mol tetrabutyl titanate is added in step (5); the rest remains the same, that is, the concentration of tetrabutyl titanate in the precursor solution is 0.15 mol / L.

[0038] like Figure 3 As shown in (a), (b), (c), (d), (e), (f), (g), and (h), the morphology of titanium dioxide on the scaffold surface changes significantly with varying precursor concentrations. When the tetrabutyl titanate concentration is 0.05 mol / L, as shown in (a), (b), (c), (d), (e), (f), (g), and (h), the morphology of titanium dioxide on the scaffold surface changes significantly. Figure 3 As shown in (a) and (b), only a small amount of nanowire-like TiO2 is observed dispersed on the surface of BaTiO3 grains, and a continuous covering layer has not yet been formed, indicating that the nucleation and growth of TiO2 are limited at this concentration; when the concentration of tetrabutyl titanate is increased to 0.08 mol / L, as Figure 3 As shown in (c) and (d), numerous nanowires and granular structures appear on the sample surface, indicating a significant increase in the nucleation density of TiO2. However, the resulting structural morphology is disordered, with localized granular accumulation. When the concentration of tetrabutyl titanate is further increased to 0.12 mol / L and 0.15 mol / L, as shown in (c) and (d), the results are as follows: Figure 3As shown in (e), (f), (g), and (h), TiO2 nucleation and growth tend to be excessive, the gaps between nanowires are gradually filled, and obvious agglomeration and densification phenomena appear in local areas. The one-dimensional nanowire characteristics begin to weaken. This indicates that although excessively high precursor concentration can increase the surface deposition, it is not conducive to maintaining a uniform and open nanowire network structure. In comparison, the TiO2 nanowires obtained under the condition of 0.10 mol / L tetrabutyl titanate concentration in Example 1 are optimal in terms of coverage uniformity, one-dimensional structural integrity, and openness.

[0039] Comparative Example 1 This comparative example describes the preparation of a barium titanate-titanium dioxide composite scaffold using the hydrothermal method disclosed in patent CN114195511A, including the following steps: (1) Add 5.85 mmol tetrabutyl titanate and 30 ml ethanol to a beaker, stir the mixture for 5 min, then add 10 ml glycerol, stir for 5 min, sonicate for 5 min, and transfer the mixture to a high-pressure reactor. (2) The barium titanate three-dimensional porous ceramic scaffold obtained in step (4) of Example 1 is completely immersed in the reaction vessel solution; (3) Place the high-pressure reactor in a solvothermal environment at 180 °C for 24 h, and remove the support after natural cooling; (4) Wash and dry the support with ethanol. The drying should be done at a low temperature to avoid the nanowires from collapsing due to the rapid evaporation of organic solvents. The specific steps are: dry at 60 ℃ for 24 h and dry at 80 ℃ for 24 h. (5) Place the dried support in a muffle furnace, raise the temperature to 400 ℃ from room temperature at 3 ℃ / min, hold for 1 h, cool with the furnace to complete the annealing, and obtain a barium titanate three-dimensional porous ceramic support (ET-BT) with titanium dioxide grown on the surface.

[0040] like Figure 2 As shown in (d), (e), and (f), the titanium dioxide synthesized by the ethanol solvent system in Comparative Example 1 is unevenly distributed on the surface of the barium titanate porous ceramic scaffold and is severely granular, with some exhibiting micron-sized flower-like structures. Compared with Example 1, this indicates that the conventional ethanol system precursor is more prone to premature reaction, which is not conducive to the formation of a uniform and stable one-dimensional nanowire layer of titanium dioxide on the surface of the complex three-dimensional scaffold.

[0041] Regarding the explanation of the mechanism, without limiting the scope of protection of this invention, the mechanism of action of the solvent system in Example 1 and Comparative Example 1 is explained as follows: like Figure 5As shown in (1), when ethanol meets tetrabutyl titanate, alcohol exchange mainly occurs to generate ethyl titanate, which is highly active and sensitive to water. It rapidly hydrolyzes to generate amorphous titanium dioxide precipitate when it comes into contact with trace amounts of water. In the subsequent hydrothermal reaction under high temperature and high pressure, more of the amorphous precipitate aggregates and grows. The structure-directing effect of glycerol is difficult to be fully utilized, which is not conducive to controllable growth.

[0042] like Figure 5 As shown in (2) and (3), the ethylene glycol methyl ether molecule contains both a hydroxyl group and an ether oxygen atom. When used as a solvent for tetrabutyl titanate, it first undergoes alcohol exchange, where the hydroxyl group in the ethylene glycol methyl ether replaces the butoxy group in the tetrabutyl titanate, generating an alcoholysis product. At this point, the ethylene glycol methyl ether molecule is covalently bonded to the titanium ion. Subsequently, the ether oxygen atom at the other end acts as an electron donor, coordinating to the Ti ion. 4+ In the empty d orbitals, a five-membered ring is formed, consisting of five atoms: Ti, O (hydroxyl oxygen), C, C, and O (ether oxygen). This process can continue, replacing more butoxy groups to form a more complex chelate structure. This improves the stability of the titanium precursor in the early stages of the reaction and makes it more prone to controlled reactions under subsequent solvothermal conditions. At this point, glycerol can fully exert its structure-directing effect, guiding the titanium precursor to form nanowires in an orderly manner. For three-dimensional periodic porous barium titanate scaffolds, this system also helps the precursor maintain a relatively stable state on the scaffold surface and near the pore walls, reducing the disordered deposition of free particles in the pores. This is more conducive to constructing a uniform and stable BaTiO3-TiO2 heterostructure interface and improving the structural stability and interface utilization efficiency of the composite scaffold in piezoelectric-photocatalytic applications.

[0043] Comparative Example 2 This comparative example describes the fabrication of a barium titanate-titanium dioxide composite scaffold using the direct ink writing 3D printing technology disclosed in patent CN114195511A, and includes the following steps: (1) Add the following to 30g of barium titanate powder: 6g xylene, 9g ethanol, 1.5g polyvinyl butyral (PVB), 0.3g triethyl phosphate (TEP), 0.3g polyethylene glycol (PEG), and 0.3g dibutyl phthalate (DBP). After mixing thoroughly, ball mill for 24 h to obtain barium titanate slurry. (2) Load the slurry into the printing syringe, place it in a centrifuge, and centrifuge at 5000 r / min for 1 min to remove bubbles, so as to obtain the piezoelectric ceramic slurry to be used; load the piezoelectric ceramic slurry into the syringe and place it on the direct writing molding platform; adjust the slurry extrusion pressure of the syringe to a suitable value (so that it can be continuously extruded without breaking the line), and then start 3D printing; after printing, let the printed product stand at room temperature to dry for 24 h to obtain the green body support; (3) After the above-printed scaffold is placed in an air atmosphere for 24 h, it is removed from the substrate and transferred to a muffle furnace for sintering. The sintering process is as follows: heat up to 325 ℃, hold for 60 min, then heat up to 500 ℃, hold for 100 min, continue to heat up to 600 ℃, hold for 120 min, and finally heat up to 1325 ℃, hold for 120 min, and cool naturally to complete the preparation of barium titanate ceramic scaffold.

[0044] (4) The solution preparation steps are the same as in Example 1. The direct ink writing 3D printed barium titanate porous ceramic support from step (3) is completely immersed in the reaction vessel solution. (5) The solvothermal reaction is the same as in Example 1; (6) The annealing step is the same as in Example 1, to obtain a barium titanate porous ceramic scaffold with titanium dioxide nanowires grown on the surface.

[0045] like Figure 2 As shown in (g) of Comparative Example 2, the porous ceramic scaffold prepared by direct ink writing printing still exhibits nanowire structures on its surface, indicating that the precursor system can induce in-situ growth of titanium dioxide on the barium titanate scaffold surface. Compared with the scaffold obtained in Example 1, the scaffold obtained in Comparative Example 2 shows more obvious local rough areas and morphological discontinuities on its surface, and the uniformity and continuity of titanium dioxide nanowire coverage are relatively poor, with local areas showing nanowire accumulation or insufficient coverage. These results indicate that the barium titanate scaffold obtained by photopolymerization 3D printing has better surface quality, is more conducive to the uniform contact of the precursor solution on the complex three-dimensional pore wall surface, and promotes the continuous and uniform in-situ growth of titanium dioxide nanowires on the scaffold surface.

[0046] Comparative Example 3 The difference between this comparative example and Example 1 is that 30 ml of ethylene glycol methyl ether and 20 ml of glycerol were added in step (5); the rest remained the same.

[0047] Comparative Example 4 The difference between this comparative example and Example 1 is that 40 ml of ethylene glycol methyl ether and 10 ml of glycerol were added in step (5); the rest remained the same.

[0048] like Figure 2As shown in (h) and (i), the surface morphology of the samples obtained in Comparative Examples 3 and 4 differs from that in Example 1, indicating that the ratio of ethylene glycol methyl ether to glycerol affects the in-situ growth of titanium dioxide nanowires. In Comparative Example 3, the amount of ethylene glycol methyl ether was lower than in Example 1. Although titanium dioxide nanowire structures could be formed on the sample surface, more particulate deposits and local agglomerations appeared, reducing the uniformity and openness of the nanowire layer. This indicates that when the relative content of ethylene glycol methyl ether is low, its alcohol exchange and coordination stabilization effect on tetrabutyl titanate is weakened, and the titanium precursor is more prone to uncontrolled homogeneous reactions. In Comparative Example 4, the amount of ethylene glycol methyl ether was higher than in Example 1. The growth of titanium dioxide nanowires on the sample surface was relatively insufficient, with some barium titanate grains exposed and insufficient coverage continuity. This indicates that when the content of ethylene glycol methyl ether is high, the structure-directing effect of glycerol is relatively weakened, which is not conducive to the formation of a continuous and uniform one-dimensional nanowire layer. The above results indicate that when the volume ratio of ethylene glycol methyl ether to glycerol is controlled at 2.3:1, it is more beneficial to balance the stability of the titanium precursor and the structure-directing effect of glycerol, thereby constructing a higher quality BaTiO3-TiO2 heterointerface.

[0049] Application examples The composite scaffold (EG-BT) prepared in Example 1, the composite scaffold (ET-BT) obtained in Comparative Example 1, and the pure barium titanate scaffold (BT) without titanium dioxide loading prepared in Example 1 were placed in 100 mL of Rhodamine B solution with a concentration of 10 mg / L and subjected to degradation tests under the same ultrasonic (40 kHz, 120 W) and light source output power (18.6 W) conditions.

[0050] Test results are as follows Figure 4 As shown, the degradation rate of the EG-BT scaffold reaches 82.32% after 30 minutes, with a corresponding first-order reaction constant of 0.059 min. -1 In contrast, the degradation rate of the BT scaffold after 90 min was 26.13%, with a corresponding first-order reaction constant of 0.004 min. -1 The degradation rate of the ET-BT scaffold after 90 min was 68.21%, corresponding to a first-order reaction constant of 0.013 min. -1 Within 90 minutes, the self-degradation of the dye is negligible, with a k value of only 0.0003 min. -1 .

[0051] The composite scaffold prepared in Example 2 was subjected to degradation tests under the same ultrasonic and light irradiation conditions. The results showed that the solution color gradually lightened with prolonged reaction time. The composite scaffold prepared in Example 3 was also subjected to degradation tests under the same ultrasonic and light irradiation conditions, and the results showed that the Rhodamine B solution also faded. This indicates that barium titanate-titanium dioxide composite scaffolds with organic pollutant degradation activity can be prepared under the following conditions: barium titanate photosensitive slurry solid content of 45-55 Vol%, ethylene glycol methyl ether to glycerol volume ratio of (2-3):1, solvothermal reaction temperature of 160-200℃, and annealing temperature of 350-450℃. This demonstrates that the method of the present invention is feasible within the above-mentioned process range.

[0052] The composite scaffold prepared in Comparative Example 2 was subjected to degradation tests under the same ultrasonic and light irradiation conditions. The results showed that the Rhodamine B solution gradually lightened with increasing reaction time, indicating that the scaffold possesses certain organic dye degradation activity. However, compared with the composite scaffold prepared by photopolymerization 3D printing in Example 1, the degradation effect of the scaffold obtained in Comparative Example 2 was relatively weak. This result indicates that the regular three-dimensional porous structure and good surface quality formed by photopolymerization 3D printing are beneficial to the uniform wetting of the precursor solution on the inner and outer surfaces of the scaffold and the uniform in-situ growth of titanium dioxide nanowires, thus being more conducive to constructing a stable and effective BaTiO3-TiO2 heterointerface and improving piezoelectric-photocatalytic performance.

[0053] The composite scaffolds prepared in Comparative Examples 3 and 4 were subjected to degradation tests under the same ultrasonic and light irradiation conditions. The results showed that the Rhodamine B solution gradually lightened with increasing reaction time, indicating that both scaffolds possessed certain piezoelectric-photocatalytic degradation activity. However, compared to Example 1, the degradation effects of Comparative Examples 3 and 4 were reduced. Therefore, a volume ratio of ethylene glycol methyl ether to glycerol deviating from approximately 2.3:1 in Example 1 is detrimental to obtaining optimal piezoelectric-photocatalytic degradation effects.

[0054] The above results indicate that the composite scaffold prepared by the method of the present invention exhibits good application performance in the degradation of Rhodamine B. Compared with the BT scaffold without TiO2 loading and the ET-BT scaffold prepared using the ethanol system, the EG-BT scaffold has a higher degradation rate constant and a shorter efficient degradation time, indicating that the ethylene glycol methyl ether-glycerol system used in the present invention is more conducive to constructing an effective heterogeneous interface and leveraging the comprehensive advantages of three-dimensional scaffolds in recyclable piezoelectric-photocatalysis.

[0055] The embodiments described above are some, but not all, of the embodiments of the present invention. The detailed description of the embodiments of the present invention is not intended to limit the scope of the claimed invention, but merely to illustrate selected embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.

Claims

1. A method for preparing a barium titanate-titanium dioxide composite scaffold based on photopolymerization 3D printing, characterized in that, Includes the following steps: S1: Using photopolymerization 3D printing technology, a three-dimensional porous ceramic blank is prepared from a photosensitive slurry containing barium titanate powder; S2: Degreasing, carbon removal and sintering are performed on the three-dimensional porous ceramic green body to obtain a three-dimensional porous barium titanate ceramic scaffold. S3: Immerse the three-dimensional porous barium titanate ceramic scaffold in a precursor solution containing a titanium source, ethylene glycol methyl ether, and glycerol for a solvothermal reaction; S4: Annealing the scaffold after the solvothermal reaction yields a barium titanate-titanium dioxide composite scaffold with in-situ grown titanium dioxide nanowires on the surface.

2. The preparation method according to claim 1, characterized in that, In step S1, the volume fraction of barium titanate powder in the photosensitive paste is 45-55 Vol%, and the average particle size of the barium titanate powder is 200-300 nm.

3. The preparation method according to claim 2, characterized in that, The components of the photosensitive paste also include trimethylolpropane triacrylate, 1,6-hexanediol diacrylate, polypropylene glycol, photoinitiator, dispersant, and rheology modifier; the photoinitiator includes diphenyl (2,4,6-trimethylbenzoyl)phosphine oxide, the dispersant includes KMT-3331, and the rheology modifier includes BYK-405.

4. The preparation method according to claim 1, characterized in that, In step S1, the exposure energy density of the photopolymerization 3D printing is 55~265 mJ / cm². 2 The scanning interval is 0.02~0.03 mm, and the layer thickness is 30 μm; in step S2, the degreasing is carried out in an argon atmosphere, and the carbon removal and sintering are carried out in an air atmosphere.

5. The preparation method according to claim 1, characterized in that, In step S3, the titanium source includes tetrabutyl titanate, the concentration of tetrabutyl titanate in the precursor solution is 0.05~0.15 mol / L, and the volume ratio of ethylene glycol methyl ether to glycerol is 2~3:

1.

6. The preparation method according to claim 1, characterized in that, In step S3, the temperature of the solvothermal reaction is 160~200 °C, and the reaction time is 24 h.

7. The preparation method according to claim 1, characterized in that, In step S4, the annealing temperature is 350~450 ℃, and the holding time is 1~2 h.

8. The preparation method according to claim 1, characterized in that, After the solvothermal reaction in step S3 and before the annealing treatment in step S4, a stepwise drying step is also included: first, keep warm at 60°C for 12~24 h, and then keep warm at 80°C for 12~24 h.

9. A barium titanate-titanium dioxide composite scaffold obtained by the preparation method according to any one of claims 1 to 8.

10. The application of the barium titanate-titanium dioxide composite scaffold as described in claim 9 in the degradation of organic pollutants, characterized in that, The degradation is carried out under conditions of light and mechanical vibration, and the organic pollutant includes Rhodamine B.

Citation Information

Patent Citations

  • Preparation method and application of barium titanate ceramic support with titanium dioxide nanowire array hydrothermally grown on surface

    CN114195511A